Human computer interaction concepts, methodologies, tools, and applications (Information Science Reference, an imprint of IGI Global, 2016)
Presents research on user interfaces for advanced technologies and how these interfaces can facilitate new developments in the fields of robotics, assistive technologies, and computational intelligence. This four-volume reference includes chapters on topics pertaining to system usability, interactive design, mobile interfaces, virtual worlds, and more.